An examplary application of mathematics teaching based on formative assessment - Aytaç Kurtuluş; Hilal Özcan (International Journal of Assessment Tools in Education)
Mathematics, by nature, has a spiral structure. The fact that the students fail to acquire an achievement in the mathematics course negatively affects other achievements. Therefore, students' mathematics failure continues exponentially. In this context, it is important to identify and eliminate students’ weaknesses, if any, with the formative assessments in the learning process. The present study aimed to improve the success level of the students with the formative assessment-based teaching practice about circle and circular region in secondary school seventh-grade mathematics teaching and implement an exemplary application for formative assessment-based teaching.Since the study sought to evaluate the learning process of the students and eliminate the weaknesses identified in the process, an action research design, one of the methods of qualitative research, was used. The study was carried out with 34 seventh-grade secondary school students. Data were collected and analyzed descriptively through observation, interview and various formative assessment tools used in the process. At the end of the three-week implementation period, substantial improvement was observed in the achievements of low and medium-achieving students, and the overall success of the students changed positively at the end of the process.